2020
DOI: 10.3390/polym12091965
|View full text |Cite
|
Sign up to set email alerts
|

Life-Cycle Assessment and Acoustic Simulation of Drywall Building Partitions with Bio-Based Materials

Abstract: The ecological transition is a process the building industry is bound to undertake. This study aimed to develop new bio-based building partition typologies and to determine if they are suitable ecological alternatives to the conventional non-renewable ones used today. This work started with the development of a bio-based epoxy composite board and a waste-based sheep wool acoustic absorbent. Six different partition typologies combining conventional and bio-based materials were analyzed. A drywall partition comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…A comparison of the data in Table 3 makes the environmental impact of the evaluated insulators visible. The environmental point of view also resonates in the work of Quintana-Gallardo et al [36]. They state that the building industry is responsible for one-third of the total carbon emissions in the world.…”
Section: Compositesmentioning
confidence: 89%
See 1 more Smart Citation
“…A comparison of the data in Table 3 makes the environmental impact of the evaluated insulators visible. The environmental point of view also resonates in the work of Quintana-Gallardo et al [36]. They state that the building industry is responsible for one-third of the total carbon emissions in the world.…”
Section: Compositesmentioning
confidence: 89%
“…Pennacchio et al [35] The responsibility of the building industry for one-third of the total carbon emissions in the world. Quintana-Gallardo et al [36] Biocomposite panels have significantly lower environmental impacts. Nußholz et al [37] Immersing wool in a saline solution, increasing the surface friction of the fibers and the adhesion to the cement matrix.…”
Section: The Removal Of Other Species Using Woolmentioning
confidence: 99%
“…These findings appear to be in line with some other early life-cycle studies of the use of biobased material alternatives in the building sector. For instance, Quintana-Gallardo et al [71] found a 50% decrease in the amount of CO 2 equivalent emitted when replacing plasterboard with bio-composite boards. Other studies have produced less conclusive results (e.g., [72]).…”
Section: Discussionmentioning
confidence: 99%
“…Although the insulating properties of sheep wool have been analyzed in several studies [ 8 , 9 , 10 , 11 ], there is still a need to provide this material with a more stable structure by hot or cold pressing [ 10 ] or mixing it with polymers. In this regard, synthetic polymers, such as polyester [ 12 ] or epoxy [ 13 ] are used in combination with wool fibers, while there are not many studies on natural matrices [ 14 ]. To the best of our knowledge, this is the first study regarding an acoustic panel prepared with soy protein and sheep wool fiber.…”
Section: Introductionmentioning
confidence: 99%